The Depression Anxiety Stress Scales for Youth (DASS-Y): Psychometric properties of an Arabic translation and Validation of a Shortened Form (DASS-Y-12) based on the Adult DASS-12 - Sahar Obeid; Gaelle Kanj; Amira Mohammed Ali; Marie-Anne El Khoury; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Rabih Hallit; Souheil Hallit; Feten Fekih-Romdhane (International Journal of Adolescence and Youth)
Background The present study aimed to validate the Arabic version of the Depression Anxiety Stress Scale for Youth (DASS-Y) and to evaluate the psychometric properties of a shortened 12-item version (DASS-Y-12) guided by the structure and item content of the adult DASS-12.Methods In this cross-sectional study, 758 adolescents completed the survey, using a snowball sampling technique.Results CFA indicated that the fit of the three-factor model of the DASS-Y and the DASS-Y-12 was excellent. Internal reliability of the scale was excellent in the long and short forms. Indices suggested that configural, metric, and scalar invariance was supported across gender in the long and short forms. Higher suicidal ideation and lower academic performance were significantly associated with higher depression, anxiety and stress as assessed by the DASS-Y and the DASS-Y-12.Conclusion The preliminary validation of the DASS-Y-12 suggests promising potential for clinical application in Arab countries by providing a culturally relevant tool for assessing psychological distress among adolescents.